Kingdom of the Netherlands-Curacao and Sint Maarten : 2016 Article IV Consultation Discussions-Press Release; Staff Report; and Informational Annex. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that the fiscal situation in Curacao and Sint Maarten remains relatively stable, following the debt relief in 2010, but progress on necessary fiscal and structural reforms has been slow. Curacao experienced modest growth in 2015 of 0.1 percent, reflecting a turnaround from the contraction of 1.1 percent in 2014. The economy of Sint Maarten expanded by 0.5 percent in 2015, a slowdown compared with the 1.5 percent recorded in 2014. Real GDP growth in 2016 is expected to reach 0.5 percent in Curacao and 0.7 percent in Sint Maarten. Over the medium term, growth is expected to pick up moderately to 0.9 percent and 1.3 percent for Curacao and Sint Maarten, respectively.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet